Evaluation of bone excision on occipital area of simulated human skull - Franceskides, Constantinos; Leger, T.; Horsfall, Ian; Shanker, Tobias; Adams, George John; Clasper, J.; Zioupos, Peter (Cranfield University, 2016)
Surgical effects of bone and soft tissue tumours, whether for biopsy or full excision have been researched from as early as the 1970’s [1]. These researches though have as main focus the biological (histological) rather the mechanical aspects of the effects [2]. With technological advances in biomedical and biomechanical modelling, a plethora of researchers have been exploring the possibilities of understanding [3] or even predicting musculoskeletal behaviour under different loading conditions [4]. This research is seeking to bridge these two different facets by looking into the mechanical effects bone tumour surgery might have to the structural rigidity of a simulated human skull.